Re-Inventing Africa's Development Linking Africa to the Korean Development Model - Park, Jong-Dae (Springer Nature, 2019)
This open access book analyses the development problems of sub-Sahara Africa (SSA) from the eyes of a Korean diplomat with knowledge of the economic growth Korea has experienced in recent decades. The author argues that Africa's development challenges are not due to a lack of resources but a lack of management, presenting an alternative to the traditional view that Africa's problems are caused by a lack of leadership. In exploring an approach based on mind-set and nation-building, rather than unity - which tends to promote individual or party interests rather than the broader country or national interests - the author suggests new solutions for SSA's economic growth, inspired by Korea's successful economic growth model much of which is focused on industrialisation. This book will be of interest to researchers, policymakers, NGOs and governmental bodies in economics, development and politics studying Africa's economic development, and Korea's economic growth model.